DEVELOPMENT AND ANALYSIS OF ENERGY-AWARE WIRELESS SENSOR NETWORK SIMULATION BASED ON LOW ENERGY ADAPTIVE CLUSTERING HIERARCHY IN AGRICULTURAL ENVIRONMENT SCENARIO - Pranaya Dafa Syarif, Muhamad
iii ABSTRACT DEVELOPMENT AND ANALYSIS OF ENERGY-AWARE WIRELESS SENSOR NETWORK SIMULATION BASED ON LOW ENERGY ADAPTIVE CLUSTERING HIERARCHY IN AGRICULTURAL ENVIRONMENT SCENARIO By Muhamad Pranaya Dafa Syarif NIM: 18118030 (Telecommunication Engineering Program) The increase in human activity based on internet technology demands development and innovation in this field, both in terms of quality and quantity. Currently, one of the internet-based technologies that is increasing and developing is the Internet of Things (IoT). One of the fields that is currently being intensively using IoT technology is the agriculture or agriculture industry. With the use of IoT technology in the form of sensors scattered throughout agricultural land, a technology that can integrate and collect sensor data is needed in a centralized base station, namely Wireless Sensor Network Technology. However, in its implementation, the Wireless Sensor Network has many factors that still need to be developed. One of the factors is the energy factor. The energy factor is a factor that must be considered when implementing a WSN network on agricultural land, because unlike other sensor networks, the sensor used by WSN has its own energy source without a fixed energy source. The method that can make efficient use of energy from nodes in the WSN for the energy reduction factor caused by the transmission of wireless communication sensors is the clustering method. One of the clustering methods on WSN that has been found and the most commonly used is LEACH or Low Efficent Adaptive Clustering Hierarchy. However, the LEACH algorithm still has a large enough space for development, which in the original algorithm, LEACH does not consider the remaining energy of nodes and the location of the selected CH. Therefore, in this final project, an existing LEACH-based Clustering Algorithm will be developed to create an efficient Wireless Sensor Network. In addition, in its implementation, the design of the Modified LEACH Algorithm made can be implemented in several scenarios, namely the scenario of the distribution of sensors based on their type, namely Homogeneous and Heterogeneous, as well as scenarios of the distribution of sensors based on the location of the sensor, namely random and uniform. The simulation design is carried out using the Matlab programming language. The simulation results are in the form of visualization of sensor nodes, data transmission directions, graphs of the number of operating nodes, energy use, data size, and the number of selected cluster heads. The final result shows that the performance of the modified LEACH-based Clustering Algorithm which has been designed and simulated has better performance than the original LEACH Algorithm. Keywords: IoT, Wireless Sensor Network, Energy, Clustering, Agriculture, LEACH, Nodes, Algorithm